Analisis kualitas air dan pengendalian pencemaran Sungai Bangkok di Kecamatan Gempol Kabupaten Pasuruan Jawa Timur - Sutrisno, Sutrisno; Rukmini, Rukmini; Amin, Radjali; Nasirudin, Nasirudin; Silviani, Silviani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2025)
This study analyzes the water quality and pollution control of the Bangkok River in Gempol District, Pasuruan Regency, East Java, which is increasingly under anthropogenic pressure, including industrial waste, agricultural runoff, and domestic waste. The main objective of this research is to evaluate the current water quality conditions using the Pollution Index (IP) and STORET methods, as well as to identify the primary pollutants affecting water quality. Samples were collected from three monitoring points—upstream, middle, and downstream—using grab sampling. Parameters analyzed included BOD, COD, NH3-N, DO, and fecal coliform, which were compared to Indonesia’s Class II water quality standards. The results showed that the concentrations of BOD, COD, NH3-N, and fecal coliform exceeded the threshold, particularly downstream, indicating high pollution loads. Based on the IP and STORET assessments, the river was classified as moderately to heavily polluted. These findings highlight the need for stricter industrial waste management and an integrated water management strategy to restore the river's ecosystem.